Introduction of cobaltous thiocyanate to mesoporous SBA-15 for ultrafast and high-capacity adsorption of ammonia with visual color indication - Yongsheng Li; Fuqiang Cheng; Caihui Cui; Zihui Meng; Min Xue (Materials & Design)
The development of ammonia adsorbents endowed with both high adsorption capacity and rapid adsorption kinetics represents one of the most effective pathways for ammonia capture and separation. In this work, the Lewis acid Co(II) and the hydrogen-bonding ligand SCN− were impregnated onto the mesoporous material SBA-15, which exhibits high hydrothermal stability and a large specific surface area. Thereby, a novel series of Co@SBA-15 composites was fabricated, demonstrating ultrafast, highly efficient, and reversible adsorption of NH3. Specifically, an ammonia uptake of 108.9 mg (g Co@SBA-15) −1 was achieved within 3 min at 20 °C and 0.1 MPa. Moreover, the incorporation of cobalt thiocyanate induced a noticeable color change during the adsorption process, which provides a visual indicator for determining the adsorption saturation of this absorbent. The reusability and humidity resistance of this mesoporous adsorbent were further confirmed through adsorption performance tests under humid conditions and five consecutive adsorption–desorption cycles. This work not only proposes a novel design strategy for ammonia adsorbents but also highlights the potential applications of cobalt thiocyanate-functionalized mesoporous silica materials in emergency scenarios, such as ammonia leakage incidents in industrial settings.